“AYITI CHERI”: CULTURAL ORIENTATION OF EARLY ADOLESCENTS IN RURAL HAITI - Ferguson, Gail M. (J Early Adolesc, 2013)
Adolescents are an emerging population in Haiti, particularly after the deadly 2010 earthquake. The steady penetration of U.S. culture into this poor, disaster-prone country begs the question: Do today’s adolescents possess a similar fondness for their home country, culture, and traditional family values as did Haitians of old? Or are they more oriented towards U.S. culture? Early adolescents (n = 105, M = 12.87 yrs, SD = .86) in rural Haiti reported their cultural orientation towards Haitian culture and U.S. culture as well as their family obligations beliefs. Findings revealed high Haitian orientation, very high family obligations (boys especially), and very low U.S. orientation, although adolescents who interacted more frequently with U.S. tourists and those who consumed more U.S. fast food had higher U.S. culture orientation. Despite severe challenges, rural Haitian early adolescents demonstrate remarkable allegiance to their home country, culture, and traditional family values.